PENINGKATAN KETERAMPILAN MEMBACA PUISI DENGAN PEMBELAJARAN KONTEKSTUAL KOMPONEN PEMODELAN DI SEKOLAH DASAR - Lehana, Lehana; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of study is for describe use of contexstual learning modeling components that could improve skills reading student poetry in the class III SDN 20 Pontianak Selatan. This research use approach qualitatif, method that used descriptive with form research action class and is collaborative. The research held in SDN 20 Pontianak Selatan, class III that numbered 29 students with subject research teacher and students class III. Technique collectors data that used that is technique observation, technique interview and technique scrutiny document with tool collectors data that is guidelines interview, sheet instrument assessment ability teacher plan learning, sheet instrument assesment ability teacher doing learning, and document results read students. Assesment ability teacher designing learning form cycle I 3,34 categorized good and increased on cycle II 3,73 categorized very well increased 0,39 from cycle I. Assesment ability teacher doing learning from cycle I 3,11categorized good and increased Incycle II 3,63 categorized very good increased 0,52 from cycle I. Assessmet results read poetry students from cycle I 71,26% and increased on cycle II 79,31% increased 8,05 % form cycle I. Based on data that obtained could concluded that happen enhancement on every cycle. With thereby, research use learning contextual component modeling on learning read poetry class III SDN 20 Pontianak Selatan could improve skills students read poetry. Keywords: Enhancement, Read Poetry , Learning Contexstual Component Modeling.